SOCIAL MEDIA AND ITS ROLE IN THE PRODUCTION AND NUTRITION OF CRISES: "ANALYTICAL STUDY OF A SAMPLE OF TWITTER DURING THE GULF CRISIS 2017" - Yssaad, Zahia (ALBAHITH ALALAMI, 2020)
Social networking sites have become very popular since the beginning of the current decade and have become linked to our daily life. We follow the news, Analyses and opinions on the one issue in a way that attracts millions of users and the number grows every secon On Twitter, one of the most important social networking sites, all social groups rushed from the president to the last citizen to open accounts when they found themselves forced to do so . During the recent Gulf crisis, Twitter was buzzing with Twitter, which achieved the largest circulation globally. Instead of serving the issue and directing it to serve the Arab interest, most of the publications were on the negative side ; The publications spread hatred and eliminate what remained among the Arab peoples. The negative exploitation of technology fueled the diplomatic crisis and created other political, social and economic crises in the form of Hitler’s propaganda.